STRATEGI KOMUNIKASI PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI SEKOLAH DASAR SATHYA SAI DENPASAR - I Nengah Dana Wijaya; I Gede Januariawan; Ni Wayan Sariani Binawati (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
This research discusses the strategy of learning communication held by the teacher of Hindu religion and character at Sathya Sai Elementary School Denpasar. Sathya Sai Elementary School Denpasar is a school that applies human values in learning process. The human values is highly regarded as the core of human character. The students’ character need to be developed through appropriate strategy of learning communication. The writer would like to find out: 1) How the strategy of learning communication; 2) How the application of learning media; and 3) What constraints are faced by the teacher; in relation with Hindu religion and character lesson. The three research questions are analyzed by humanistic and behavioral learning theories. This research is a qualitative descriptive one with phenomenological approach. It makes use of purposive sampling method. The main informant is the teacher of Hindu religion and character lesson and the supporting informants are the head of the school and some students. The data are collected by instruments, such as: researcher direct observation, interview and documents study. The data obtained are analyzed by using the Miles and Huberman analysis model. The findings of the research show that: 1) The strategy of learning communication held by the teacher of Hindu religion and character at Sathya Sai Elementary School Denpasar is of humanistic and behavioral methods. The teacher makes use of multy ways communication model and behaves as motivator and facilitator in the learning process. The teacher emphasizes her communication on greeting, praying, silent sitting and students’ selfaffirmation to begin the lesson. While closing the lesson she encourages the students to thank God, the teacher and each other for the knowledge has been learned. 2) The teacher utilizes several types of learning medias, such as: school text-book, other books of Hindu religion, like Bhagavadgita, character contained story books and audio visual media. Besides that the teacher also makes use of internet and social media features, such as: facebook, youtube and whatsapp group. 3) Some obstacles sometimes still occur during learning process.